Characteristics of lactic acid bacteria, microbial community and fermentation dynamics of native grass silage prepared in Inner Mongolian Plateau - Hou, Meiling; Wang, Zhijun; Sun, Lin; Jia, Yushan; Wang, Shicong; Cai, Yimin (Frontiers in Microbiology, 2023)
Introduction To prepare high-quality silage, we studied the chemical composition, silage fermentation, characterization, and identification of lactic acid bacteria (LAB) associated with the silage fermentation of native grass on the Inner Mongolian Plateau. Methods LAB were isolated from fresh native grass and their silage, and silages were prepared using a small-scale fermentation system with 2–3 cm length in plastic bags. Results The dominant species of native grasses used were Stipa baicalensis, Leymus chinensis, Cleistogenes squarrosa, Melissilus ruthenicus and Pulsatilla turczaninovii, which contained 47.83–59.43 % moisture, 55.12–67.74 % neutral detergent fiber (NDF), and 8.72–14.55 crude protein (CP), and these nutrients did not change greatly during ensiling. Good preservation with a relatively low pH (below 4.44) and high (p < 0.05) lactic acid content (>0.58) was obtained after ensiling. Based on the morphological and biochemical characteristics, these isolates were divided into 12 groups (A-L). All isolate strains were gram-positive and catalase-negative bacteria that produce lactic acid from glucose. Group A-K were cocci, while group L was rod-shaped. Group A-E formed D-lactic acid, but group H-K formed L-lactic acid, and other groups formed DL-lactic acid. Group A-E were heterofermentative, and Group F-L were homofermentative types of LAB. According to the 16S rRNA gene sequences analysis, strains were identified as genus Leuconostoc (A, B, and C), Weissellla (D, E), Pediococcus (F, G), Enterococcus (H, I, J and K), and Lactiplantibacillus (L). Enterococcus (E.) faecium (29.17%, percentage of total isolates) and Pediococcus (P.) acidilactici (18.75%) were the most frequently occurring dominant species. Discussion This study suggests that the native grasses contained abundant LAB species, and they can be used as good-quality silages in animal husbandry. In addition, the strains P. acidilactici and E. faecium were the most frequently isolated from native grass silages as dominant species which can be a potentially excellent inoculant for native grass silage.